2021
DOI: 10.2217/rme-2021-0019
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Multitarget Biologic Injection in the Spine: Prospective Case Series of Multitarget Platelet-Rich Plasma for Low Back Pain

Abstract: Aim: To evaluate the use of a multitarget platelet-rich plasma (PRP) injection approach for the treatment of chronic low back pain (LBP). Materials & Methods: Forty-six patients with more than 12 weeks of LBP who failed conservative treatments were injected with PRP into the facet joints, intervertebral discs, epidural space and/or paravertebral muscles. Visual analog pain scale and Roland-Morris Disability Questionnaire scores were measured at baseline and predefined intervals. Results: Mean visual analog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…The current understanding of the degenerative process in the spine and the interrelationship between the different structures of the spine suggests that the vast majority of patients with chronic low back pain do not have only one pain-generating site. In our first case series, 81.8% of the patients presented alterations in two or more sites, with facet arthrosis (91.3%) and disc degeneration (60.9%) being the most frequent [21]. Evaluation of the cause of chronic LBP is complex due to many different structures involved and the multifactorial nature of the disease process.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The current understanding of the degenerative process in the spine and the interrelationship between the different structures of the spine suggests that the vast majority of patients with chronic low back pain do not have only one pain-generating site. In our first case series, 81.8% of the patients presented alterations in two or more sites, with facet arthrosis (91.3%) and disc degeneration (60.9%) being the most frequent [21]. Evaluation of the cause of chronic LBP is complex due to many different structures involved and the multifactorial nature of the disease process.…”
Section: Discussionmentioning
confidence: 91%
“…A study previously published by our group showed good results in a protocol for the management of lumbar degenerative disease with the use of PRP in multiple painful structures of the lumbar spine, presenting the Muti Target concept [21]. The acronym PerMuTIS (Personalized Multi Target Biologic Injection in the Spine) was created to describe a concept of concurrent treatment of multiple pain generators in patients with LBP.…”
Section: Introductionmentioning
confidence: 99%
“…The remainder of patients received ESIs. A total of six studies with 218 patients received epidural PRP [ 4 , 21 , 22 , 23 , 24 , 26 ]. Lemper et al used PRP diluted in platelet-poor plasma (PPP) in one patient [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…One study included a subject with cervical and lumbar radiculopathy [ 17 ] and another two studies [ 20 , 25 ] enrolled subjects with either cervical or lumbar radiculopathy. The remaining studies included only lumbar radiculopathy [ 3 , 4 , 6 , 18 , 21 , 22 , 23 , 24 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation